2013
DOI: 10.1159/000345090
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Serum Placental Growth Factor, Pregnancy-Associated Plasma Protein-A and Free β-Human Chorionic Gonadotrophin at 30-33 Weeks in the Prediction of Pre-Eclampsia

Abstract: Objective: To investigate the potential value of maternal serum concentrations of free β-human chorionic gonadotrophin (β-hCG), pregnancy-associated plasma protein-A (PAPP-A) and placental growth factor (PlGF) at 30-33 weeks of gestation in the prediction of pre-eclampsia (PE) developing at or after 34 weeks. Methods: Serum free β-hCG, PAPP-A and PlGF were measured at 11-13 and at 30-33 weeks of gestation in a case-control study of 50 cases that developed PE at or after 34 weeks and 250 unaffected controls. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 42 publications
(71 reference statements)
3
29
0
3
Order By: Relevance
“…6 In another study by Lai et al, median PLGF level in all PE cases and late PE cases was significantly lower compared to controls with PLGF level as 25.1, 27.2 and 34.7 pg/ml respectively. 2 The Poon et al study with base-cohort population of 7797 singleton pregnancies, including 34 case subjects also had similar findings.…”
Section: Performance Of Plgf (Biochemical Marker)mentioning
confidence: 58%
See 4 more Smart Citations
“…6 In another study by Lai et al, median PLGF level in all PE cases and late PE cases was significantly lower compared to controls with PLGF level as 25.1, 27.2 and 34.7 pg/ml respectively. 2 The Poon et al study with base-cohort population of 7797 singleton pregnancies, including 34 case subjects also had similar findings.…”
Section: Performance Of Plgf (Biochemical Marker)mentioning
confidence: 58%
“…3 Various other studies comparing the role of PLGF versus other biochemical markers have been done using AUC. 2,10 In these studies PLGF has emerged as of best predictive value with maximum AUC for prediction of PE. 2 In one of the pioneer studies involving large number (n=5,099) of pregnant females where 145 developed PE (2.84%), Lai et al found AUC of 0.734 for late PE cases.…”
Section: Plgf As a Screening Toolmentioning
confidence: 99%
See 3 more Smart Citations